Experimental and computational studies on the electronic excited states of nitrobenzene. (November 2016) - Krishnakumar, Sunanda; Das, Asim Kumar; Singh, Param Jeet; Shastri, Aparna; Rajasekhar, B.N.
Abstract: The gas phase electronic absorption spectrum of nitrobenzene (C6 H5 NO2 ) in the 4.5–11.2 eV region is recorded using synchrotron radiation with a view to comprehend the nature of the excited states. Electronic excited states of nitrobenzene are mainly classified as local excitations within the benzene ring or nitro group and charge transfer excitations between the benzene and nitro group, with some transitions showing percentage from both. The nature of molecular orbitals, their orderings and energies are obtained from density functional theory calculations which help in assigning partially assigned/unassigned features in earlier photoelectron spectroscopy studies. Optimized geometry of ionic nitrobenzene predicts redistribution of charge density in the benzene ring rather than the nitro group resulting in stabilization of the benzene ring π orbitals in comparison to the neutral molecule. Time dependent density functional theory computations are found to describe the experimental spectra well with respect to energies, relative intensities and nature of the observed transitions in terms of valence, Rydberg or charge transfer type. New insights into the interpretation of 1 B2u ← 1 A1g and 1 B1u ← 1 A1g shifted benzene transitions in light of the present computational calculations are presented. The first few members of the ns, np and nd type Rydberg series in nitrobenzene, converging to the first six ionization potentials, identified in the spectra as weak but sharp peaks are reported for the first time. In general, transitions to the lowest three unoccupied molecular orbitals 4b1, 3a2 and 5b1 are valence or charge transfer in nature, while excitations to higher orbitals are predominantly Rydberg in nature. This work presents a consolidated experimental study and theoretical interpretation of the electronic absorption spectrum of nitrobenzene. Highlights: Electronic spectra of nitrobenzene in 4.5–11.2 eV region using synchrotron radiation. Molecular orbital energies and orderings obtained using DFT. Vertical excited state energies using TDDFT and correlation with experiment. New insights into interpretation of valence and charge transfer transitions. First report of Rydberg series of ns, np and nd type converging to first six IPs.